2016
DOI: 10.1116/1.4952409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vacuum thermal annealing to encapsulated graphene field effect transistors

Abstract: Water vapor barriers used for graphene encapsulation can both exclude water from the environment and trap water in the device, preventing annealing from improving device performance. In this paper, the authors investigate the effects of vacuum annealing on encapsulated single layer graphene field effect transistors (SLG-FETs). The stability of GFETs is monitored for a period of up to six months, and different annealing times and atmospheres are tested to recover lost electronic performance. Fabricated encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…24 In our experiments we observe that if the annealing is done on a finished device, it drastically increases the contact resistance from 1-10 X to more than 100 kX, rendering the device impractical. However, if the annealing is performed before the lithography process, the final device has the usual contact resistance ranging from 1 to 10 X, while the mobility increases.…”
Section: -2mentioning
confidence: 74%
“…24 In our experiments we observe that if the annealing is done on a finished device, it drastically increases the contact resistance from 1-10 X to more than 100 kX, rendering the device impractical. However, if the annealing is performed before the lithography process, the final device has the usual contact resistance ranging from 1 to 10 X, while the mobility increases.…”
Section: -2mentioning
confidence: 74%
“…This result suggests that limits on ∆n sat are primarily due to atmospheric gases absorbed on the graphene, rather than defects that are healed by high temperature annealing in UHV [42][43][44][45][46] . However, the increase in ∆n sat from 700 to 900 K annealing temperature indicates these adsorbates are not fully removed even by anneals up to 700 K. This observation is difficult to reconcile with data from several groups indicating desorption temperatures for H 2 O on graphene from 150 K to 400 K [47][48][49] . It is well established that H 2 O, O 2 , H 2 , and N 2 intercalate between monolayer graphene and its substrate (in many cases SiC) 48,[50][51][52][53][54][55][56][57][58][59][60] .…”
mentioning
confidence: 94%
“…However, the increase in ∆n sat from 700 to 900 K annealing temperature indicates these adsorbates are not fully removed even by anneals up to 700 K. This observation is difficult to reconcile with data from several groups indicating desorption temperatures for H 2 O on graphene from 150 K to 400 K [47][48][49] . It is well established that H 2 O, O 2 , H 2 , and N 2 intercalate between monolayer graphene and its substrate (in many cases SiC) 48,[50][51][52][53][54][55][56][57][58][59][60] . On the other hand, it is not straightforward to identify a mechanism by which these intercalants would affect the doping efficiency of surface Li adatoms.…”
mentioning
confidence: 94%
“…19 High temperature annealing under different atmospheres (including N 2 , H 2 , H 2 / Ar, and vacuum) is one of the effective ways to clean PMMA from the graphene surface and improve the electrical performance to that of ideal graphene. [20][21][22] Hong et al reported that PMMA membrane with Pd nanoparticles on graphene shows high response and good selectivity to hydrogen because the Pd nanoparticles enhance the sensor response and the PMMA membrane blocks gas molecules with higher molecular weight. 23 Beyond this, very little is known on the effect of PMMA residues on gas sensing at present.…”
Section: Introductionmentioning
confidence: 99%